Гендерна асиметрія в юридичній термінології - Лисенко, Ольга Сергіївна; Lysenko, O. S. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто процес елімінації граматичних та лексичних засобів сексизму в англійській юридич¬ній термінології та заміни їх на гендерно-нейтральні терміни. Зокрема, звернуто увагу на механізм конструю¬вання гендеру за допомогою маркованих суфіксів жіночого роду та їх функціонування у терміносистемі права англійської мови на сучасному етапі в рамках упровадження норм гендерно коректної мови та впливу інших екстралінгвістичних факторів на цей процес. The article is dedicated to the elimination process of the grammar and lexical methods to mark sexism in the legal English terminology and introduction of the gender neutral terms. The problem is studied in the aspect of the gender construction by means of the marked feminine suffixes (-a, -ster, –ess, -trix), their productivity in the new terms’ formation, functioning of the feminitative terms in the legal English term system, its gender interpretation in the framework of the legal discourse at the modern period of time, the influence of the gender correct language norms on the above mentioned process as well as the impact of extra linguistic factors on it. It is proved in the article that the present gender relationship and stereotypes affect the legal English term system as being an unalienable part of the human’s social activity. It is also refuted that the gender neutral character of the legal English term system is its immanent feature.
The Gender Asymmetry in the Legal Terminology
Keywords: гендерно маркований; gender marked; гендерно нейтральний; gender neutral; термін; term